55.6k views
2 votes
Subtract these polynomials (3x^3-4x^2+x-2)-(x^3-5x^2+3x+2)

User Destroyer
by
5.4k points

2 Answers

2 votes
The answer is 2x^3 + x^2 -2x - 4
User Priebe
by
6.0k points
6 votes

Answer:
2x^3+x^2-2x-4

Explanation:

Given the expression:


(3x^3-4x^2+x-2)-(x^3-5x^2+3x+2)

It is important to remember the multiplication of signs:


(+)(+)=+\\(-)(-)=+\\(+)(-)=-

Then, knowing this, we can distributive the negative sign:


=3x^3-4x^2+x-2-x^3+5x^2-3x-2

The final step is to add the like terms. Then we get:


=2x^3+x^2-2x-4

User Protector One
by
5.6k points